The Roles of Long Non-coding RNA in Osteoporosis - Li, Ying; Li, Jinglan; Chen, Leilei; Xu, Liangliang (Current Stem Cell Research & Therapy, 2020)
The Human Genome Project (HGP) announced in 2001 that it had sequenced the entire human genome, yielding nearly complete human DNA. About 98.5 percent of the human genome has been found to be non-coding sequences. Long non-coding RNA (lncRNA) is a non-coding RNA with a length between 200 and 100,000 nucleotide units. Because of shallow research on lncRNA, it was believed that it had no biological functions, but exists as a by-product of the transcription process. With the development of high-throughput sequencing technology, studies have shown that lncRNA plays important roles in many processes by participating in epigenetics, transcription, translation and protein modification. Current researches have shown that lncRNA also has an important part in the pathogenesis of osteoporosis. Osteoporosis is a common disorder of bone metabolism, also a major medical and socioeconomic challenge worldwide. It is characterized by a systemic reduction in bone mass and microstructure changes, which increases the risk of brittle fractures. It is more common in postmenopausal women and elderly men. However, the roles of lncRNA and relevant mechanisms in osteoporosis remain unclear. Based on this background, we hereby review the roles of lncRNA in osteoporosis, and how it influences the functions of osteoblasts and osteoclasts, providing reference to clinical diagnosis, treatment and prognosis of osteoporosis.
Keywords: lncRNA